Composition-structure-property (Zn2+ and Ca2+ ion release) evaluation of Si-Na-Ca-Zn-Ce glasses: potential components for nerve guidance conduits - Zhang, X. F.; Kehoe, S.; Adhi, S. K.; Ajithkumar, Thalasseril G.; Moane, S.; O'Shea, H.; Boyd, D. (Materials Science & Engineering C-Materials for Biological Applications, 2011)
Bioactive glasses have demonstrated tailored therapeutic ion release, primarily with respect to the augmentation of hard tissues. However, controlled degradation and release of therapeutic ions from biomaterials may also play an important role in soft tissue regeneration such as repair of peripheral nerve discontinuities. In this study, three silica based glasses (0.5SiO(2)-0.2CaO-0.13ZnO-XNa2O-(0.17-X) CeO2) where, (0.04 < X < 0.14) were synthesised and characterised. The local environment of the Si-29 isotope was probed for each glass using Si-29 MAS-NMR, whilst the thermal characteristics of each glass were examined using DTA. Following these analyses, ion release profiles for Ca2+ and Zn2+ were evaluated; an equivalent specific surface area of 1 m(2) of each glass powder was incubated (37 degrees C) in 10 ml of citric acid buffer and TRIS-HCl buffer solution (pH 3.0 and pH 7.4 respectively) for incubation periods of up to 30 days. The Zn2+ concentration of each filtrate was analysed using flame Atomic Absorption Spectroscopy (Varian AA240FS Fast Sequential AAS) and the Ca2+ concentration of each filtrate was determined using Inductively Coupled Plasma-Mass Spectrometer (Varian 820 ICP-MS). Results obtained from the Si-29 MAS-NMR spectra indicated Q(2) structures pervading the network. An analytical model was proposed to analyse the ion release profiles for each glass, and indicated heterogeneous dissolution of glass networks. The ion release data demonstrates that ion release in the range (19.26-3130 ppm) for Ca2+ and in the range (5.97-4904 ppm) for Zn2+ occurred. Release of such elements, at appropriate levels, from peripheral nerve guidance conduits may be advantageous with respect to the repair of peripheral nerve discontinuities. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Dissolution; Modelling